Analisis Penerapan Metode Eksperimen Materi Rangkaian Listrik Kelas VI SD N Tlogosari Kulon 01 Semarang - Amiliya Nurul Jannah; Kartinah Kartinah; Ariani Nur Setyawati (Journal on Education, 2024)
The aim of this research is to describe the application of experimental methods to electrical circuit material at SD Tlogosari Kulon 01. This type of research is descriptive qualitative. Data collection methods are observation, documentation and questionnaires. Data analysis uses triangulation. Application of experimental methods to electrical circuit material in elementary schools in accordance with the planned steps. The results of observations from implementing learning activities using experimental methods make students active and enthusiastic in learning. In documentation analysis, students carried out activities well and were able to understand electrical circuits. In the questionnaire results, it was found that most students were interested in learning activities using experimental methods.